Unlocking Statistical Insights: Global Classroom Collaboration with Universitas Islam Negeri Sultan Syarif Kasim Riau Indonesia Leaves a Lasting Impact - Chuan, Zun Liang (Pusat Sains Matematik (PSM), 2024)
On May 8, 2024, a global classroom session was conducted via the Google Meet platform, organized collaboratively by the Department of Mathematics, Universitas Islam Negeri Sultan Syarif Kasim Riau Indonesia, and Pusat Sains Matematik (PSM), Universiti Malaysia Pahang Al-Sultan Abdullah.